Thermoelastic behavior of advanced composite sandwich plates by using a new 6 unknown quasi-3D hybrid type HSDT - Mantar, JL (2015)
This paper presents an analytical solution for the thermoelastic bending analysis of advanced composite sandwich plates by using a new quasi-3D hybrid type HSDT with 6 unknowns which is based on a generalized formulation. In addition, the nonlinear term of the temperature field is included in the generalized mathematical formulation in such way that it can be freely chosen and if desired can be different from the shear strain shape functions of the displacement field. So, infinite quasi-3D hybrid type HSDTs with just 6 unknowns can be derived from the present generalized formulation. The thermoelastic bending governing equations are obtained through the principle of virtual works and solved via Navier Method. Interesting results are obtained and compared with quasi-3D and 2D HSDTs. Transverse shear stress results are strongly influenced by nonlinear temperature field and for different HSDTs different results are produced. Therefore should be further discussed in the literature.